Phagocytic activity of chicken peritonial macrophage against Salmonella typhimurium poultry isolates - Bhattacharya, Asis; Singh, V P; Gupta, L K (The Indian Journal of Animal Sciences, 2012)
Phagocytic index (PI) of chicken peritoneal macrophages was assayed in resident and protease peptone elicited macrophages after in vitro infection with 4 S. typhimurium poultry isolates, E 1841 (nonvirulent), E 2336 (less virulent), E 2187 and E 2385 (virulent) and a virulent reference European strain F 98. Higher phagocytic index of elicited chicken peritoneal macrophages after in vitro infection with S. typhimurium isolates. The PI of resident chicken peritoneal macrophages ranged from 123±4.22 (with reference strain F 98) to 182±6.05 (with isolate E 2336). The maximum PI of elicited macrophages was observed with isolate B 1841 (230.25±4.98) and lowest with reference strain F 98 (159.75 ± 3.73).